DESIGN OF CMOS LOW DROP-OUT REGULATORS: A COMPARATIVE STUDY (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
The advancement in battery operated portable devices, noise sensitive devices and other devices, which need high precision supply voltages has fuelled the growth of Low Drop-Out Regulators. Low Drop-Out Regulators showed advantage over its counterpart. The design of Low Drop-Out Regulators with high performance and less Die area is challenging problem now-a-days. This paper is a study of various techniques that are used to achieve better performance of low drop-out regulators.Â